Towards a brain like computer - 1 - Aswin s/o Jayakumar (Nanyang Technological University, 2023)
In recent years, neuroscientists and nanoscientists have been working together to map the activity of the entire human brain and the eye. This ambitious project aims to unlock the mysteries of these complex systems and shed light on how they function. By combining technology such as LM393 and Light Emitting Diodes, the author hopes to create a comprehensive map of the neural circuits and pathways that underlie perception, cognition, and behavior. This research has the potential to improve the understanding of the brain and the eye. However, it is also an enormous challenge, requiring the collaboration of intense research from multiple disciplines and the development of new methods and tools. Despite these challenges, progress is being made, and the field is rapidly advancing towards its goal of mapping the activity of the human brain and eye at unprecedented levels of detail.